2022
DOI: 10.3390/children9040570
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Motor-Developmental Outcomes in Infants with a Critical Congenital Heart Defect

Abstract: Infants with critical congenital heart defects (CCHDs) are at increased risk for neurodevelopmental delays. The early identification of motor delays is clinically relevant to prevent or reduce long-term consequences. The current study aims to describe the motor-developmental pathways of infants with a CCHD. Motor development was assessed in 215 infants and toddlers using the Dutch version of the Bayley-III. At 3 months (n = 165), 9 months (n = 188), and 18 months (n = 171) the motor composite scores were 97, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 57 publications
2
12
1
Order By: Relevance
“…Last, mean gross motor score for single-ventricle physiology at 18 months was 7.5±3.7 versus 10.6±3.1 for TGA, 10.2±2.8 for TOF, and 9.6±2.6 for aortic arch pathology ( P =0.001). 123…”
Section: Congenital Cardiovascular Defects and Kawasaki Diseasementioning
confidence: 99%
“…Last, mean gross motor score for single-ventricle physiology at 18 months was 7.5±3.7 versus 10.6±3.1 for TGA, 10.2±2.8 for TOF, and 9.6±2.6 for aortic arch pathology ( P =0.001). 123…”
Section: Congenital Cardiovascular Defects and Kawasaki Diseasementioning
confidence: 99%
“…7 A few studies have reported lower gross motor than fine motor scores. 3,4,[8][9][10][11][12] Reporting motor standard scores or composite scores without the individual subtest scaled scores masks differences between fine and gross motor scores and thus may decrease the recognition of individual deficits and reduce recommended clinical neurodevelopmental interventions. 8,[11][12][13][14][15] Recognising that long-term motor delays may be improved by early interventions, there is a need to study gross motor and fine motor scores separately to aid clinicians in the care of this population.…”
mentioning
confidence: 99%
“…3,4,[8][9][10][11][12] Reporting motor standard scores or composite scores without the individual subtest scaled scores masks differences between fine and gross motor scores and thus may decrease the recognition of individual deficits and reduce recommended clinical neurodevelopmental interventions. 8,[11][12][13][14][15] Recognising that long-term motor delays may be improved by early interventions, there is a need to study gross motor and fine motor scores separately to aid clinicians in the care of this population. [4][5][6]14 Reported acute care predictors of adverse motor outcomes have included a variety of different cardiac defects, especially for those after palliative surgery, imaging determined brain injury, need for anticoagulant medication, longer duration of mechanical ventilation, and longer hospital and intensive care stay.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The continued management of the condition is dependent on postoperative care and rehabilitation since the success rate of surgery has significantly increased [ 1 , 2 ]. According to American Heart Association guidelines published in 2012, primary care providers were encouraged to refer CHD children who had undergone cardiac surgery for early developmental evaluation and intervention [ 3 ]. At present, the majority of these programs are designed for children who are preschool or school-aged, and infants with CHD who have undergone surgery but do not yet have access to a standardized cardiac rehabilitation (CR) program; additionally, postoperative CR and evaluation indexes of cardiac function and motor development in the infant population are still unexplored [ 4 ].…”
mentioning
confidence: 99%